Factors Associated with Obesity Incidence in the Military Command XIV/Hasanuddin Makassar (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2022)
The prevalence of obesity in Indonesia over the age of 18 years old is around 21.8%, South Sulawesi 19.1%, and Makassar is 24.05%. The highest prevalence in South Sulawesi, is higher than the prevalence rate of South Sulawesi and the national. The purpose  of this study was to determine the factors related to the obesity of army in XIV/Hasanuddin Kesdam Unit in 2021. The research method of this study used  a cross sectional study with 92  total sample whose has been taken with simple random sampling method. The results showed that there were a relationship among family health  history (p = 0.003), energy intake (p = 0.000), and physical activity (p = 0.016)  and obesity in Kesdam XIV/Hasanuddin Makassar army.  The conclusion of this study is that if one or both of the respondent's parents have obesity record and excessive energy intake, it will be  associated with obesity. Therefore, sufficient physical activity will prevent the obesity.